REVEALING ANOMALIES BY NETWORK PACKET FLOODING ON BUILT FTP AND OPENSSH SERVERS IN CONTROLLED LAB ENVIRONMENT: REVEALING ANOMALIES BY NETWORK PACKET FLOODING ON BUILT FTP AND OPENSSH SERVERS IN CONTROLLED LAB ENVIRONMENT - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
This scientific paper investigates the effects of network packet flooding on FTP (port 21) and SSH (port 22) protocols, aiming to reveal and document anomalies in server behavior under high-load conditions. By simulating packet flooding in a controlled lab environment, an analysis on vulnerabilities and anomalies unique to each protocol is conducted in order to the improve defensive capabilities. The results provide guidance on best practices to secure FTP and OpenSSH services against malicious traffic, such as Distributed Denial of Service (DDoS) attacks, supporting wider network security strategies.